ASUHAN KEPERAWATAN PADA IBU NIFAS DENGAN GANGGUAN ELIMINASI: INTKONENSIA URINE - Nina Sunarti (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2022)
The postpartum period begins after the birth of the placenta and ends when the uterine organs return to their pre-pregnancy state. Because the birth process will result in loosening of the muscles in the vagina. One way to restore vaginal muscles to the mother after the puerperium is kegel exercise. Exercise can be performed regularly by tightening and relaxing the muscles that support the bladder and urethra. Efforts to tighten the pelvic muscles will prevent a woman from experiencing or reduce the risk of inability to control micturition. The objective of this study was to gain real experience in providing nursing care to normal postpartum mothers with urinary incontinence elimination disorders. This study was a case study approach to postpartum mothers through the nursing process icluding assessment, diagnosis, intervention, implementation and evaluation of nursing. Kegel exercise can be done for two days of hospitalization but can't be done optimally on the mother because there are wounds and pain in the episiotomy. However, the mother's knowledge about kegel exercises has increased so that this exercise can be continued at home independently. Kegel exercise can be done after the puerperium gradually and if there are no more complaints of pain in the episiotomy wound.